THE IMPORTANCE OF STRENGTHENING STUDENT SOFT SKILLS BY HIGHER EDUCATION INSTITUTION IN PRE-INTERNSHIP PROGRAM - Jana Sandra; Ade Suryana, Sunarmin (Adisam Publisher, 2024)
There are many advantages and benefits of internships for students. One of the advantages of an internship is that it broadens your knowledge regarding the world of work. Various kinds of insights, starting from the scope of duties and responsibilities of work, teamwork, adding new knowledge and expertise. However, unfortunately, there are still many students who do not have adequate soft skills during internships. This is a qualitative research with a phenomenological approach. Phenomenology is a form of qualitative research that focuses on the study of an individual’s lived experiences. So, we can learn from the experiences of others. This research is aimed at answering the question of how universities equip their students with soft skills before taking part in internships and what complaints there are from companies regarding the quality of students who take part in internships at their companies. Data collection was carried out using semi- structured interviews to HRD managers and university students who have taken internship program. This research proves that there are still many students who do not have soft skills consisting of intrapersonal and interpersonal communication, so they receive many complaints from companies or government institutions. For this reason, strengthening students' soft skills needs to be optimized during pre- internship training.